Analisis Pembagian Warisan Melalui Hibah di Yayasan Inhil Peduli Tembilahan - Novita, Renny; Herdiansyah; Ariwibowo, R. Dimas; Komala, Fitri; Avandi, Mohd (Jurnal Indragiri Penelitian Multidisiplin, 2023)
In this journal, the author will examine and analyze the practice of dividing inheritance at the Inhil Peduli Tembilahan foundation, which uses Islamic legal sources instead of avoiding inheritance law using the Islamic law method but using the grant method. In the process of making this journal, the author uses a qualitative approach and a library method in which the author obtains data through interviews, observation, documentation and collects material through books and several other online media. Based on the results of the researcher's analysis, the distribution of inheritance at the Inhil Cares Tembilahan foundation does not use the Islamic law method but uses the practice of grants. In terms of dividing this inheritance, the kyai, ustadz and ustadzah who have fields of knowledge turn a lot away from the Qur'an and Sunnah but rather for the priority of the people or what is also known as maslahah mursalah, where the goal is to avoid disputes and conflicts as well as problems around the kyai's family and the foundation itself. And in the distribution of inheritance, the implementation is based on what has been agreed upon by all related parties and has a relationship and is carried out for maslahah mursalah for many people.